The Alternative Concepts of Blasphemy Law in Indonesia: Legal Comparison with Ireland and Canada - Loresta Cahyaning Lintang; Adriano Martufi; J.W. Ouwerker (BESTUUR, 2021)
Indonesia has recognized and implemented blasphemy law within its legal system. Nevertheless, by many scholars, it is considered ambiguous and "no perimeter", which leads to the question of its legal certainty. Blasphemy is different across religions and legal systems, particularly in Ireland and Canada. This study seeks to examine how Indonesia, Ireland, and Canada rule blasphemy. To analyze information about the regulation of blasphemy in those countries, a comparative legal approach is utilized. The result of this study shows that blasphemy laws are heterogeneously written by the national legislation of Indonesia, Ireland, and Canada. Irish blasphemy law includes the element of mens rea, protect all religions in the country. Irish government clearly defines blasphemy law as a limitation of the freedom of expression. Canada does not regulate its blasphemy law strictly but use precedents to maintain the certainty and predictability. Mirroring to these two countries, Indonesian blasphemy law should be reconstructed into five ways: expanding the protected religions to include the minority religions, defining explicit limitations, specifying mens rea element, measuring the ‘threat to public’ elements, and more professional law enforcement officers.